Do TOEFL iBT® Scores Reflect Improvement in English‐Language Proficiency? Extending the TOEFL iBT Validity Argument. (19th May 2014) - Ling, Guangming; Powers, Donald E.; Adler, Rachel M.
Abstract: One fundamental way to determine the validity of standardized English‐language test scores is to investigate the extent to which they reflect anticipated learning effects in different English‐language programs. In this study, we investigated the extent to which the TOEFL iBT ® practice test reflects the learning effects of students at intensive English programs in the United States and China, as well as extracurricular English‐learning activities that may be associated with the expected learning effects. A total of 607 students at the high school level or beyond participated in the United States and China, including 111 students who took 2 forms of the practice test under a pretest and posttest design. The results showed moderate to substantial levels of improvement on each of the TOEFL iBT sections, with different score gain patterns for students in the United States and China. We concluded that students who study at English programs similar to those included in this study can improve their English‐language proficiency levels at least moderately over 6 months or longer, as indicated by changes in their scores on the TOEFL iBT practice test. This improvement is consistent with an interpretation of TOEFL iBT scores as indicators of English‐language proficiency. Abstract : Report Number: ETS RR–14–09